Interruption of anti-thymocyte globuline treatment in solid organ transplantation is effectively monitored through a low total lymphocyte count - Rasander, Rikke Olund; Sørensen, Søren Schwartz; Krohn, Paul Suno; Bruunsgaard, Helle (Frontiers in Immunology, 2024)
Anti-Thymocyte Globulin (ATG) is a cornerstone in immune suppression for solid organ transplantation. The treatment is a balance between complications arising from overimmunosuppression such as infections and cancer versus rejection stemming from underimmunosuppression. CD3 + T-lymphocyte measurements are frequently employed for treatment monitoring. However, this analysis is costly and not always accessible. The aim of this study was to investigate whether the total count of lymphocytes could replace CD3 + T-lymphocyte measurements based on data from our transplantation center combined with a review of the literature. The hypothesis was that the total lymphocyte count could serve as a diagnostic surrogate marker for CD3 + T-lymphocytes. A retrospective cohort study was conducted, including patients who underwent kidney and/or a pancreas transplantation and received ATG as induction therapy or for rejection treatment. The inclusion criterium was that the total lymphocyte count and CD3 + T-lymphocyte measurements were measured simultaneously on the same day. Additionally, PubMed and Embase were searched up to 18/10/2023 for published studies on solid organ transplantation, ATG, Tlymphocytes, lymphocyte count, and monitoring. In the retrospective cohort study, a total of 91 patients transplanted between 2016 and 2023, with 487 samples, were included. Total lymphocyte counts below 0.3 x 10 9 /L had a high sensitivity (86%) as a surrogate marker of CD3 + T-lymphocytes below 0.05 x 10 9 /L, but the specificity was low (52%) for total lymphocyte counts above 0.3 x 10 9 /L as a surrogate marker for CD3 + T-lymphocytes above 0.05 x 10 9 /L. A review of the literature identified seven studies comparing total lymphocyte counts and CD3 + T-lymphocytes in ATG monitoring. These studies supported the use of a low total lymphocyte count as a surrogate marker for CD3 + T-lymphocytes and an indicator to omit ATG treatment. However, there was no consensus regarding high total lymphocyte counts as an indicator for continued treatment. In conclusion, the total lymphocyte count can be used to omit ATG treatment when below 0.3 x 10 9 /L whereas the CD3 + T-lymphocyte analysis should be reserved for higher total lymphocyte counts to avoid ATG overtreatment.